Inhibition of overexpressed Kv3.4 augments HPV in endotoxemic mice - Turzo, Maurizio; Metzger, Karin; Lasitschka, Felix; Weigand, Markus A.; Busch, Cornelius (BMC pulmonary medicine, 2020)
Hypoxic pulmonary vasoconstriction (HPV) is a reaction of the pulmonary vasculature upon hypoxia, diverting blood flow into ventilated areas to preserve oxygenation. It is impaired in endotoxemia or ARDS. Voltage gated potassium channels have been shown to play a key role in the regulation of HPV. The aim of the study was to identify a voltage gated potassium channel involved in dysregulated HPV during endotoxemia.